Effects of Implementation of The Policy on Postponing Benefits on Performance of the State Civil Apparatus at DKI Jakarta Provincial Government - Vivi Febriyanti; Vid Adrison (Jurnal Manajemen Pelayanan Publik, 2022)
This study research views relation between incentives and enhancement of unit’s performance budget which is managed by human resources in DKI Jakarta Provincial Government. In this research using 62,568 data which is classified by 1,738 unit from 2017 – 2019 related to realization of budget and human resources.  By using Difference in Difference method in this research find that after implementing policy in delayed of incentives, it has a positive impact on realization budget of 12.75% in units affected by the policy with a significance level of 1%. In addition, the implementation the policy if the unit can not achieve the target  for two (2) concecutive months has a positive effects of 7.10% with significance level of 1%. This study recommends that the policy can be implemented if government concern in gender, education, and employee attendance in each unit, so the unit can achieve the target.  The findings research support the literature that policy which is includes the punishment has positive effects in improving performance unit and motivating employee performance.